On the erugin and floquet-lyapunov theorems for countable systems of difference equations - Teplins’kyi, O. Yu.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For linear difference equations in the space of bounded number sequences, we prove an analog of the Erugin theorem on reducibility and present sufficient conditions for the reducibility of countable linear systems of difference equations with periodic coefficients.